Non-paper providing an overview of the main points made in the briefing sessions arranged by the Geneva Group of Commonwealth developing countries and ACP group of states on the proposals for modifications in the Agreement of Anti-Dumping Practices (WTO [Geneva]CH, 2008)
Deals with five proposals for modification of the Agreement viz. extension of special and differential treatment to developing countries; use of zeroing in the calculation of margins for dumping; lesser-duty rule and public interest; anti-circumvention; and, duration of anti-dumping duties.
Keywords: DUMPING